اللغة الانفعالية في الأبنية الصرفية - البحيري، إيمان شعبان جودة مرسي (جامعة الأزهر - كلية اللغة العربية بجرجا, 2024)
تناولت هذه الدراسة اللغة الانفعالية بوصفها أداة إنسانية معبرة تحمل قيما انفعالية معينة، وحاولت من خلال هذه الدراسة بيان أهمية الوظيفة الانفعالية للغة، وحضورها في المستوى الصرفي، والكشف عن الجوانب التعبيرية والنواحي الانفعالية الكامنة في الأبنية والظواهر الصرفية وتحليلها؛ للوقوف على أبعادها الدلالية النفسية، وبيان دورها في توجيه المعنى. وجاءت الدراسة في تمهيد تناول مفهوم اللغة الانفعالية، وأنماطها، وحاولت من خلال مباحثها الستة عرض الأبنية الصرفية وتحليلها بغية بيان دورها في الكشف عن المناحي الانفعالية النفسية. وخلصت الدراسة إلى أن هذه الأبنية تحمل طاقة تعبيرية مؤثرة ساهمت في تصوير الجانب الانفعالي للموقف الذي وردت فيه. This study dealt with emotional language as an expressive human tool that carries certain emotional values. Through this study, I tried to demonstrate the importance of the emotional function of language, its presence at the morphological level, and to reveal and analyze the expressive and emotional aspects hidden in morphological structures and phenomena. To understand its psychological semantic dimensions, and to explain its role in directing meaning. The study included an introduction that dealt with the concept of emotional language and its patterns. Through its six sections, I tried to present and analyze the morphological structures in order to explain their role in revealing emotional and psychological aspects. The study concluded that these buildings carry an influential expressive energy that contributed to portraying the emotional side of the situation in which they were mentioned.
Keywords: علم الصرف -- الدلالات التعبيرية -- اللغة العربية -- النحو العربي -- الأبنية الصرفية